Pengaruh Dispsin Kerja, Lingkungan Kerja Terhadap Kinerja Pegawai Dinas Lingkungan Hidup, Kehutanan Dan Pertanahan Provinsi Papua Barat Daya - Amir Husein Siregar; Yolanda E. S. Litaay; Ibrahim Nauw; Andi Irwan (STIM-LPI Makassar, 2026)
This study aims to understand in-depth how work discipline and the work environment influence employee performance at the Environment, Forestry, and Land Agency of Southwest Papua Province. A qualitative research approach was used to explore employee perceptions, experiences, and actual practices through semi-structured interviews and participant observation. The results indicate that work discipline positively contributes to task effectiveness, while a conducive work environment strengthens motivation and collaboration among employees. These findings are relevant to theories of work motivation and organizational culture and have implications for the development of human resource management.